2014
DOI: 10.5194/acp-14-8631-2014
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: On the use of nudging for aerosol–climate model intercomparison studies

Abstract: Abstract. Nudging as an assimilation technique has seen increased use in recent years in the development and evaluation of climate models. Constraining the simulated wind and temperature fields using global weather reanalysis facilitates more straightforward comparison between simulation and observation, and reduces uncertainties associated with natural variabilities of the large-scale circulation. On the other hand, the forcing introduced by nudging can be strong enough to change the basic characteristics of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
172
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(182 citation statements)
references
References 48 publications
8
172
2
Order By: Relevance
“…The horizontal winds were nudged to the ERA-Interim reanalysis with a relaxation timescale of 6 h. Temperature and humidity were not nudged, since earlier experiences have shown that directly constraining these two fields might lead to substantially different model climate (Zhang et al, 2014;Jeuken et al, 1996). Details of the nudging implementation are described in Zhang et al (2014).…”
Section: Impact On Aerosol Climatology In Cam5mentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal winds were nudged to the ERA-Interim reanalysis with a relaxation timescale of 6 h. Temperature and humidity were not nudged, since earlier experiences have shown that directly constraining these two fields might lead to substantially different model climate (Zhang et al, 2014;Jeuken et al, 1996). Details of the nudging implementation are described in Zhang et al (2014).…”
Section: Impact On Aerosol Climatology In Cam5mentioning
confidence: 99%
“…The horizontal winds were nudged to the ERA-Interim reanalysis with a relaxation timescale of 6 h. Temperature and humidity were not nudged, since earlier experiences have shown that directly constraining these two fields might lead to substantially different model climate (Zhang et al, 2014;Jeuken et al, 1996). Details of the nudging implementation are described in Zhang et al (2014). Nudging effectively constrains the large-scale circulation and suppresses the noise caused by natural variability, thus allowing for detection of changes in the simulated aerosol characteristics and their climate effects with substantially shorter simulations (see, e.g., Kooperman et al, 2012).…”
Section: Impact On Aerosol Climatology In Cam5mentioning
confidence: 99%
“…On the other hand, as nudging introduces an artificial forcing term to the prognostic equations of the model, it can significantly change the basic characteristics of the model climate, resulting in unintentional impacts on the simulated atmospheric physics and/or chemistry. For example, Lohmann and Hoose [2009] found that ECHAM5-HAM produced more convection and precipitation in the tropics when it was nudged toward the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA40 reanalysis, while Kooperman et al [2012] and Zhang et al [2014] noted that when temperature and winds in CAM5 were nudged toward the ERA-Interim reanalysis, changes were seen in the top-ofatmosphere (TOA) energy budget, convective precipitation, and the liquid and ice water paths. These studies suggest that, although nudging can reduce the impact of natural internal variability, it could also potentially cause biases.…”
Section: Introductionmentioning
confidence: 99%
“…The weaker cloud radiative effects can be explained by a lower cloud cover and a smaller liquid water path in the ECHAM-HAMMOZ simulation. Analog differences were found by Zhang et al (2014) for ECHAM6.1-HAM2.2 due to differences in nudging techniques. Zhang et al (2014) investigated the behavior of aerosol-climate models when different nudging techniques are applied compared to free running simulations.…”
mentioning
confidence: 79%
“…Analog differences were found by Zhang et al (2014) for ECHAM6.1-HAM2.2 due to differences in nudging techniques. Zhang et al (2014) investigated the behavior of aerosol-climate models when different nudging techniques are applied compared to free running simulations. In particular the additional nudging of temperature decreased the cloud radiative effects by about 5, resp.…”
mentioning
confidence: 79%